ANALISIS PERILAKU IBU DALAM MEMBERIKAN PENDIDIKAN HIGIENE MENSTRUASI PADA REMAJA PUTRI AUTIS (STUDI DI SLB NEGERI SEMARANG) - Deastuti, Nurridha; Widjanarko, Bagoes; Prabamurti, Priyadi Nugraha (Fakultas Kesehatan Masyarakat, 2018)
Adolescents with autism have resistance in controlled abstract concept, social interaction, and behavior. Various problems appearÂ when children with autism enter adolescence, especially in girls who will experience menstruation. Adolescent girls when experiencing menstruation must pay attention to their hygiene, to avoid various diseases. Poor menstrual hygiene can trigger abnormal vaginal discharge. In Indonesia around 90% of women have the potential to experience vaginal discharge. Parents, especially mothers, must play a role in providing menstrual education related to their autistic teenage girls when they enter adolescence. The purpose of this study was to describe maternal behavior in giving menstrual hygiene education to autistic girls in SLB Negeri Semarang. The research method used is a qualitative method. The subjects were 6 people who taken with purposive sampling method and data collection technique with in-depth interview. The results of this study showed that 5 mothers had provided menstrual hygiene education by way of practice, namely how to wear pads, how to clean clothes that are affected by blood, how to treat pads that have been used, and how to clean the female organs. There are differences behavior of mothers who haveÂ child with severe autism and child with mild autism. In child with severe autism, need a long time and repetitive teaching. Four mothers who have mild autistic children, the mother will be easier to educate her autistic child.